Distance learning in the COVID-19 pandemic: acceptance and attitudes of physical therapy and rehabilitation students in Turkey - Raziye Şavkın; Gökhan Bayrak; Nihal Büker (James Cook University, 2021)
Introduction: To reduce the rate of spread of the COVID-19 pandemic in Turkey, distance education was initiated in all universities on 23 March 2020. Distance learning had not been experienced in physical therapy and rehabilitation education before the COVID-19 outbreak. This study aimed to (a) determine the acceptance and attitudes of Pamukkale University Physical Therapy and Rehabilitation undergraduate students towards distance learning during the COVID-19 outbreak and (b) compare the results among years. Methods: This study was conducted from May 2020 to June 2020 at the Pamukkale University School of Physical Therapy and Rehabilitation in Turkey. A total of 381 students (271 female, 110 male) participated. The Distance Learning Systems Acceptance Scale (ease of use, benefit), the Community Feeling Scale (affective and actional dimension), and the Distance Learning Attitude Scale (general acceptance, individual awareness, perceived usefulness, effective participation) were used to measure students' acceptance and attitudes towards distance education. Results: Students had partly positive attitudes towards distance learning but were undecided about individual awareness, usefulness, and effective participation. The sense of community among students was moderate in the distance learning environment. Distance learning acceptance and attitude, and the sense of community levels, were highest in fourth-year students (last year of the school), followed by first-, third-, and then second-year students. The distance learning and sense of community scores of first- and fourth-year students were significantly higher than those of second- and third-year students (p≤0.01). Conclusion: Physical therapy and rehabilitation undergraduate students' attitudes towards distance learning during the COVID-19 outbreak were positive. However, when comparing between years, students in the second and third academic years had less positive attitudes. This may be because most of their curricula consisted of practical courses and summer field internships, and there were no opportunities to practise on mannequins, peers, and patients in distance education. In this study, the sense of community among students in the distance learning environment was also moderate. This may be because students were not enthusiastic about attending course lectures online, and because they did not have to view the lectures at a set time.